Mechanical regulation of mitochondrial morphodynamics in cancer cells by extracellular microenvironment - Lunova, Mariia; Jirsa, Milan; Dejneka, Alexandr; Sullivan, Gareth John; Lunov, Oleg (Biomaterials and biosystems, 2024)
Recently, it has been recognized that physical abnormalities (e.g. elevated solid stress, elevated interstitial fluid pressure, increased stiffness) are associated with tumor progression and development. Additionally, these mechanical forces originating from tumor cell environment through mechanotransduction pathways can affect metabolism. On the other hand, mitochondria are well-known as bioenergetic, biosynthetic, and signaling organelles crucial for sensing stress and facilitating cellular adaptation to the environment and physical stimuli. Disruptions in mitochondrial dynamics and function have been found to play a role in the initiation and advancement of cancer. Consequently, it is logical to hypothesize that mitochondria dynamics subjected to physical cues may play a pivotal role in mediating tumorigenesis. Recently mitochondrial biogenesis and turnover, fission and fusion dynamics was linked to mechanotransduction in cancer. However, how cancer cell mechanics and mitochondria functions are connected, still remain poorly understood. Here, we discuss recent studies that link mechanical stimuli exerted by the tumor cell environment and mitochondria dynamics and functions. This interplay between mechanics and mitochondria functions may shed light on how mitochondria regulate tumorigenesis.
Keywords: Mitochondria; Cancer; Mitochondrial dynamics; Mechanotransduction; Tumor metabolism